Clinical rating scale for pantothenate kinase‐associated neurodegeneration: A pilot study. Issue 11 (28th August 2017) - Darling, Alejandra; Tello, Cristina; Martí, María Josep; Garrido, Cristina; Aguilera‐Albesa, Sergio; Tomás Vila, Miguel; Gastón, Itziar; Madruga, Marcos; González Gutiérrez, Luis; Ramos Lizana, Julio; Pujol, Montserrat; Gavilán Iglesias, Tania; et al.
ABSTRACT: Background: Pantothenate kinase‐associated neurodegeneration is a progressive neurological disorder occurring in both childhood and adulthood. The objective of this study was to design and pilot‐test a disease‐specific clinical rating scale for the assessment of patients with pantothenate kinase‐associated neurodegeneration. Methods: In this international cross‐sectional study, patients were examined at the referral centers following a standardized protocol. The motor examination was filmed, allowing 3 independent specialists in movement disorders to analyze 28 patients for interrater reliability assessment. The scale included 34 items (maximal score, 135) encompassing 6 subscales for cognition, behavior, disability, parkinsonism, dystonia, and other neurological signs. Results: Forty‐seven genetically confirmed patients (30 ± 17 years; range, 6‐77 years) were examined with the scale (mean score, 62 ± 21; range, 20‐106). Dystonia with prominent cranial involvement and atypical parkinsonian features were present in all patients. Other common signs were cognitive impairment, psychiatric features, and slow and hypometric saccades. Dystonia, parkinsonism, and other neurological features had a moderate to strong correlation with disability. The scale showed good internal consistency for the total scale (Cronbach's α = 0.87). On interrater analysis, weighted kappa values (0.30‐0.93) showed substantial or excellent agreement in 85% of the items. The scale also discriminated a subgroup of homozygous c.1583C>T patients with lower scores, supporting construct validity for the scale. Conclusions: The proposed scale seems to be a reliable and valid instrument for the assessment of pediatric and adult patients with pantothenate kinase‐associated neurodegeneration. Additional validation studies with a larger sample size will be required to confirm the present results and to complete the scale validation testing. © 2017 International Parkinson and Movement Disorder Society